Teaching vocabulary to older people through different approaches - Ballardin, Isadora Rostirolla (My University, 2018)
Vocabulary is one of the main keys for a successful communication in language. However, other abilities are first presented to the students and when they have to express their feelings or just communicate, they cannot do it. This happens because they do not have enough vocabulary to talk each other, especially older people that sometimes is the first time that they are having contact with the new language. In order to start working with vocabulary for older people, it was decided to use some methods, approaches and techniques. This paper aims at finding out the results of using vocabulary from an Internship Report to increase older people lessons through different approaches. Aiming to answer what kind of results we can have teaching vocabulary for older people lessons using different approaches and techniques, analyzing an Internship Report. This study used two approaches: literature review and documental research. The study was done in the Internship IV with a group of older people from Santa Tereza Cathedral from Caxias do Sul. The main authors who discuss older people, vocabulary, and methods, approaches and techniques are Taylor (2011), Richards and Renandya (2002), Schmitt (2008), Webb (2007), LaRosa and Plump (2017), Ur and Wright, 2005), Young-Davy (2014), Marsick and Watkins (2001), Brown (2000), Martinez (2009), Richards and Rodgers (1999) and .Larsen-Freeman (2002). After the analyses of the vocabulary activities at the lesson plans templates, it was observed that, in general, the different methods, approaches and techniques were effective for older people (sic).
O vocabulário é uma das principais chaves para uma comunicação bem sucedida. No entanto, outras habilidades são primeiramente apresentadas para os alunos e quando eles precisam expressar seus sentimento ou simplesmente se comunicar, eles não conseguem. Isso acontece porque os alunos não tem vocabulário necessário para conversar, especialmente os idoso que muitas vezes está sendo a primeira vez que estão tendo contato com a nova língua. A fim de começar a trabalhar vocabulário com os idosos, foi decidido usar alguns métodos, abordagens e técnicas. Esse artigo tem como finalidade encontrar os resultados de usar vocabulário de um Relatório de Estágio para ampliar as aulas do idosos através de diferentes abordagens. Com o objetivo de responder que tipo de resultados podemos ter ensinando vocabulário para idosos, usando diferentes abordagens e técnicas analisando um Relatório de Estágio. Este estudo utilizou duas abordagens: revisão bibliográfica e pesquisa documental. O estudo foi realizado no Estágio IV com um grupo de idosos da Catedral Santa Tereza de Caxias do Sul. Os principais autores que discutem sobre os idosos, vocabulário e métodos, abordagens e técnicas são Taylor (2011), Richards and Renandya (2002), Schmitt (2008), Webb (2007), LaRosa and Plump (2017), Ur and Wright, 2005), Young-Davy (2014), Marsick and Watkins (2001), Brown (2000), Martinez (2009), Richards and Rodgers (1999) and .Larsen-Freeman (2002). Após a análise das atividade de vocabulário, observou- se que, em geral os diferentes métodos, abordagens e técnicas foram eficazes para os idosos (sic).
Keywords: Older people; Vocabulary; Teaching